Humanization of Primary Health Care: healthcare network Management and local governance - Ferreira Granja, Gabriela; Campos Pavone Zobol, Elma Lourdes (O Mundo da Saúde, 2012)
The humanization of the Brazilian National Healthcare System requires interactive and participatory relationships of professionals, managers and users by means of a healthcare network. The organization of this network begins in Primary Care. The network organizes the services that directly or indirectly provide equitable and comprehensive health services based on the needs of a certain population. Local governance facilitates the communication of the different actors in the network, promotes a joint action of State and civil society and marks a new frontier in the relationship of citizens and administration. In order to humanize healthcare it is necessary a good and effective governance by providing opportunities for those involved in the healthcare network to establish a covenant of tasks and responsibilities; exchange knowledge; strength social control; defragment organization and work processes; decrease the distance between rulers and ruled. Such spaces of deliberation reinforce the democratic character of public policy and have a potential to foster citizenship, people empowerment and humanization of health care.